CLINICAL EVALUATION OF ANTI-OXIDANT ACTIVITY OF MUSTA (CYPERUS ROTUNDUS LINN.) WITH SPECIAL REFERENCE TO OBESITY (STHAULYA) (International Journal of Ayurveda and Pharma Research, 2015)
Obesity is a health problem of affluence, of worldwide prevalence and is considered as the insidious creeping pandemic which is now engulfing the entire world. Obesity induces oxidative stress which is partly responsible for morbidities. The modern science fails to give a safe and effective remedy. Ayurveda can pave a way towards attaining the goal. In Ayurveda Charaka has mentioned Musta (Cyperusrotundus Linn.) in Lekhaniyamahakashay i.e. drugs acting as scraping agents. The rhizomes of Musta (Cyperusrotundus Linn.) contains flavonoids, ascorbic acid and polyphenol which are responsible for its anti oxidant activity. Open labelled study was done on 60 patients at Ayurved Mahavidyalaya Sion, Mumbai-22 for duration of 90 days. Out of 60 patients, 30 were advised to take Mustachurna 3 gm thrice a day with warm water along with diet and exercise while 30 patients were advised diet and exercise only. Monthly assessment was done on the basis of signs and symptoms like Atitrushna (excessive Thirst), Atiksudha (excessive hunger), Atinidra (excessive sleepiness), Atisveda (excessive sweating), Daurgandhya (excessive body odour), Anutsaha (laziness), Daurbalya (tiredness) and Kshudraswasa (breathlessness). Objective improvement was done on the basis of BMI, Waist: Hip ratio, and MDA (Malondialdehyde), GSH (glutathione peroxidase) enzyme study for oxidant activity at baseline and at the end of study (after 90 days). Subjective improvement is shown in percentage. Paired t test was applied to objective parameters which was highly significant at 1% level of significance i.e. p